Disorientation and Moral Life - Harbin, Ami (New York Oxford University Press, 2016)
Disorientation are human experiences of losing one's bearings that can paralyze, overwhelm, embitter, and misdirect moral agents. In this philosophical exploration of disorientation and its significance for action, A M I Harbin demonstrates through a distinctly feminist perspective that in some cases of disorientation, individuals gain new forms of awareness of political complexity and social norms, and new habits of relating to others in an unpredictable moral landscape.
Include References and Index
Keywords: Orientation -- Ethics, Modern -- Feminist theory